2014
DOI: 10.1111/cge.12371
|View full text |Cite
|
Sign up to set email alerts
|

SLC26A2 disease spectrum in Sweden – high frequency of recessive multiple epiphyseal dysplasia (rMED)

Abstract: Diastrophic dysplasia (DTD) is an autosomal recessive skeletal dysplasia caused by SLC26A2 mutations. Clinical features include short stature, joint contractures, spinal deformities, and cleft palate. SLC26A2 mutations also result in other skeletal dysplasias, including the milder recessive multiple epiphyseal dysplasia (rMED). DTD is overrepresented in Finland and we speculated that this may have influenced the prevalence and spectrum of SLC26A2-related skeletal conditions also in Sweden. We reviewed the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The second couple had the c.214A>T (p.K72X) variant of SLC26A2. This gene is associated with autosomal recessive achondrogenesis type IB, atelosteogenesis type 2, diastrophic dysplasia, and multiple epiphyseal dysplasia 4 14 . The third couple had the HSD3B2 c.776C>T (p.T259M) variant.…”
Section: Discussionmentioning
confidence: 99%
“…The second couple had the c.214A>T (p.K72X) variant of SLC26A2. This gene is associated with autosomal recessive achondrogenesis type IB, atelosteogenesis type 2, diastrophic dysplasia, and multiple epiphyseal dysplasia 4 14 . The third couple had the HSD3B2 c.776C>T (p.T259M) variant.…”
Section: Discussionmentioning
confidence: 99%
“…An overlap between the phenotypes of the SLC26A2 dysplasia family have been observed [ 13 , 30 , 31 , 35 ] and this was evident also in individual cases and cohorts described in the recent literature ( Table 4 ). Some subjects with rMED have shown clinical manifestations that are more characteristic for DTD like cleft palate, auricular defects and severe cervical kyphosis [ 30 , 31 , 35 ]. The normal or mildly shortened stature seen in rMED can help to clinically distinguish it from DTD.…”
Section: Discussionmentioning
confidence: 77%
“…Clubfoot is a rare radiological finding that has been observed mostly in association with rMED. In a previous study [28], rMED patients with clubfoot were reported to carry homozygous/compound heterozygous mutations in SLC26A2 at birth. In addition, Superti-Furga et al [29] described rMED patients with normal stature, clubfoot, and double-layered patellae caused by a DTDST mutation.…”
Section: Discussionmentioning
confidence: 99%